2007
DOI: 10.1126/science.1146812
|View full text |Cite
|
Sign up to set email alerts
|

Menin Controls Growth of Pancreatic ß-Cells in Pregnant Mice and Promotes Gestational Diabetes Mellitus

Abstract: During pregnancy, maternal pancreatic islets grow to match dynamic physiological demands, but the mechanisms regulating adaptive islet growth in this setting are poorly understood. Here we show that menin, a protein previously characterized as an endocrine tumor suppressor and transcriptional regulator, controls islet growth in pregnant mice. Pregnancy stimulated proliferation of maternal pancreatic islet b-cells that was accompanied by reduced islet levels of menin and its targets. Transgenic expression of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
324
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(346 citation statements)
references
References 29 publications
15
324
2
5
Order By: Relevance
“…It has recently been shown that prolactin represses islet menin levels and stimulates beta cell proliferation during pregnancy in mice. It was found that the transgenic expression of the gene encoding menin in maternal beta cells inhibited islet expansion and led to the development of GDM phenotypes [35]. In human studies, inadequate compensatory insulin secretion in the face of increased insulin resistance has consistently been observed in patients with GDM [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that prolactin represses islet menin levels and stimulates beta cell proliferation during pregnancy in mice. It was found that the transgenic expression of the gene encoding menin in maternal beta cells inhibited islet expansion and led to the development of GDM phenotypes [35]. In human studies, inadequate compensatory insulin secretion in the face of increased insulin resistance has consistently been observed in patients with GDM [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The same is probably true in obese non-diabetic humans, although the increase in beta cell mass (about 50%) is less than that seen in mice [13]. Also, during pregnancy the maternal pancreatic beta cell mass increases both in rodents and humans to meet the increased physiological demands [6,14,15]. There is plenty of evidence for replication being the primary mechanism for beta cell mass expansion during obesity-induced insulin resistance and pregnancy in mice [7,9,[16][17][18].…”
Section: Introductionmentioning
confidence: 87%
“…Transgenic menin overexpression in β cells prevents islet expansion, which leads to maternal hyperglycemia (29). Therefore, transgenic menin mice exhibit features of human gestational diabetes (29). For these reasons, ZEB1, as a transcription factor, may be involved in the pathogenesis of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…BCL-6 represses menin, a product of the Men1 gene, expression. Transgenic menin overexpression in β cells prevents islet expansion, which leads to maternal hyperglycemia (29). Therefore, transgenic menin mice exhibit features of human gestational diabetes (29).…”
Section: Discussionmentioning
confidence: 99%